HIV-specific CD8 T Cell Cross-reactivity Following Ad5-based Vaccination Is Shaped by Vaccine Regimen and Prior Ad5 Exposure. (4th October 2017) - Boppana, Sushma; Sterett, Sarah; Qin, Kai; Bansal, Anju; Goepfert, Paul
Abstract: Background: A major obstacle to developing an HIV vaccine is its enormous viral diversity. As such, the ability of the CD8 T cell response to cross-recognize several variants of a single epitope could be an important factor in optimizing future vaccine design. Some prior work has indicated that CD8 cross-reactivity may play a role in viral control in individuals with protective HLA-I alleles; however, not much is known about CD8 cross-reactivity in the context of HIV vaccination. Methods: We examined the CD8 T cell cross-reactivity in recipients of two prior preventative HIV-1 vaccine studies, both of which used adenovirus serotype 5 (Ad5) vectors: HVTN 502 (MRKAd5) and HVTN 505 (VRC DNA with Ad5 boost). We measured the responses to vaccine-encoded epitopes and their common variants using IFNγ ELISpot assays. We also quantified the antigen sensitivities by measuring the IFNγ responses to log fold serial peptide dilutions. Results: Overall, CD8 responses to variant epitopes had a lower magnitude and decreased antigen sensitivity than those targeting vaccine-encoded epitopes ( P < 0.0001 and P = 0.014). A greater number of mutations, less conservative amino acid substitutions, and HLA-I driven mutations negatively affect the immunogenicity of cross-reactive responses ( P < 0.0001, P = 0.0003, and P < 0.0001, respectively). Additionally, cross-reactive responses had a higher magnitude in MRKAd5 recipients with low pre-existing Ad5 titers than those with high pre-existing titers ( P = 0.0230). Among that former MRKAd5 group, cross-reactive responses were decreased in magnitude and proportion in comparison with cross-reactive responses of VRC DNA/Ad5 recipients ( P = 0.0052, P = 0.0488), even though both groups' responses to vaccine-encoded epitopes had similar magnitudes. Conclusion: Our data show that cross-reactive responses are frequently elicited by vaccination and that this cross-reactivity is affected by the vaccine regimen and by pre-existing Ad5 titers. Future work will focus on analyzing the TCR clonotype repertoire responsible for these CD8 T cell responses and establishing the biologic and clinical significance of these vaccine-induced cross-reactive CD8 T cells. Disclosures: All authors: No reported disclosures.